Pengaruh Media Aplikasi Perubahan Energi Berbasis Android Terhadap Hasil Belajar IPA Siswa Kelas III SDN 10 Palembang - Djunaidi Djunaidi; Amiruddin Amiruddin; Anisa Ayu Rusnely (Journal on Education, 2024)
Science learning in elementary schools which is less varied is the cause of students' difficulties and lack of learning outcomes. Therefore, there is a need for learning media that can help students be active in learning. The aim of this research is to determine the effect of using Android-based Energy Change Application Media on Science Learning Material on Energy Change Class III at SDN 10 Palembang. This type of research is Pre-Experimental and uses a One-Group Pretest-Posttest Research Design consisting of one class, namely class III. The population was 23 students and the sample was 23 students. Data analysis techniques are descriptive statistics and inferential statistical data analysis. Based on the Pretest results, the average score for student learning outcomes is 35 with a very low score of 10, so it can be said that the level of students' ability to understand the test and mastery of science material before using the Android-based Energy Change Application media is relatively low. Meanwhile, the average score after learning using the Android-based Energy Change Application media (posttest) was 81.52 from 23 students, 21 students met the minimum completeness criteria (KKM) or were in the high category. The results of inferential analysis using the t-test showed that tcount = 2.608 and ttable = 2.079, so we obtained tcount>ttable or 2.608>2.079, as well as with the normality test, sig values ​​of more than > 0.05, the data is normal. Based on this research, it can be concluded that the Android-based Energy Change Application Media has an influence on science learning outcomes on energy change material in class III at SDN 10 Palembang.